America's own goal: Who pays the tariffs? - Julian Hinz; Aaron Lohmann; Hendrik Mahlkow; Anna Vorwig (Kiel Institute for the World Economy, 2026)
The 2025 US tariffs are an own goal: American importers and consumers bear nearly the entire cost. Foreign exporters absorb only about 4% of the tariff burden - the remaining 96% is passed through to US buyers. Using shipment-level data covering over 25 million transactions valued at nearly 4 trillion, we find near-complete pass-through of tariffs to US import prices. US customs revenue surged by approximately 200 billion in 2025 - a tax paid almost entirely by Americans. Event studies around discrete tariff shocks on Brazil (50%) and India (25-50%) confirm: export prices did not decline. Trade volumes collapsed instead. Indian export customs data validates our findings: when facing US tariffs, Indian exporters maintained their prices and reduced shipments. They did not "eat" the tariff. – – Die US-Zölle von 2025 sind ein Eigentor: Amerikanische Importeure und Verbraucher tragen nahezu die gesamten Kosten. Ausländische Exporteure absorbieren nur etwa 4% der Zolllast - die restlichen 96% werden an US-Käufer weitergegeben. Auf Basis von Lieferungsdaten mit über 25 Millionen Transaktionen im Wert von fast 4 Billionen Dollar finden wir eine nahezu vollständige Weitergabe der Zölle an die US-Importpreise. Die US-Zolleinnahmen stiegen 2025 um etwa 200 Milliarden Dollar - eine Steuer, die fast ausschließlich von Amerikanern bezahlt wird. Ereignisstudien zu diskreten Zollschocks gegen Brasilien (50%) und Indien (25-50%) bestätigen: Exportpreise fielen nicht. Stattdessen brachen die Handelsvolumina ein. Indische Exportzolldaten validieren unsere Ergebnisse: Konfrontiert mit US-Zöllen hielten indische Exporteure ihre Preise und reduzierten ihre Lieferungen. Sie "schluckten" den Zoll nicht.
Keywords: 330; Tariffs; Trade Policy; Pass-Through; Import Prices; United States; Zölle; Handelspolitik; Importpreise; Vereinigte Staaten